PENGEMBANGAN STRATEGI PEMBELAJARAN ACTIVE LEARNING BERBANTUAN MEDIA PROYEKTOR UNTUK MENINGKATKAN KONSENTRASI DAN KEAKTIFAN BELAJAR FIQIH SISWI MADRASAH ALIYAH - Kamilatus Sholihah; Abdus Syakur (STKIP Subang, 2026)
This study was motivated by the low level of concentration among female students during Fiqh learning, which is primarily caused by the continued use of conventional teacher-centered instructional methods. Such learning approaches often limit students' active participation, reduce their motivation, and hinder their understanding of Fiqh concepts. Therefore, there is a need to develop an innovative learning strategy that actively engages students in the learning process. The objective of this study is to develop an Active Learning-based Fiqh learning strategy that can improve the concentration of female students at Madrasah Aliyah (MA) during classroom instruction. This study employed a Research and Development (R&D) methodology consisting of several stages, namely needs analysis, instructional design, product development, implementation, evaluation, and revision. Data were collected through classroom observations, interviews, questionnaires, and documentation, and were analyzed using descriptive qualitative and quantitative techniques to evaluate the effectiveness of the developed learning strategy. The findings indicate that the implementation of the Active Learning-based Fiqh learning strategy successfully increased students' concentration, participation, motivation, and engagement throughout the learning process. Students demonstrated greater enthusiasm in participating in discussions, asking and answering questions, solving learning tasks, and collaborating effectively in group activities. Furthermore, the developed strategy was considered practical, feasible, and effective as an alternative instructional approach because it promotes an interactive, student-centered, and enjoyable learning environment. Consequently, the strategy contributes to improving the quality of Fiqh learning and supports the achievement of better learning outcomes for female students at Madrasah Aliyah.